Using transcriptome analysis to evaluate the impact of dsAllim cotton on non-target organism O. similis - Li, Changyan; Yao, Haiqin; Hua, Kunwei; Cao, Danyang; Zhang, Hang; Yin, Desuo; Zhang, Xiaolian; Wang, Feng; Ma, Weihua; Chen, Lizhen; You, Aiqing (Frontiers in Plant Science, 2026)
IntroductionThe application of genetically engineered (GE) crops in pest management raises biosafety concerns among governments, the scientific community, and the public, especially with the emergence of RNA interference (RNAi)-based crops expressing insecticidal double-stranded RNA (dsRNA). These crops may pose challenges to public health, agriculture, and conservation, and they could also present risks to non-target organisms, including beneficial natural enemies of pests. Natural enemies of insects are a significant component of global biodiversity and play a crucial role in managing insect pests within agroecosystems. This study addresses the biosafety concerns associated with insect-resistant transgenic dsRNA-expressing crops, focusing on their potential unintended effects on non-target organisms, particularly natural enemies.MethodsWe combined biological and bioinformatic approaches, utilizing both food-chain delivery and animal-feeding systems, to comprehensively evaluate the potential unintended effects of exogenous insecticidal dsRNA expressed by dsAllim cotton on the biological parameters and transcriptome of the cotton-field predatory natural enemy, Orius similis.ResultsThe findings indicate that dsAllim cotton had no adverse effects on O. similis, suggesting its potential safety for non-target beneficial insects. At both developmental and transcriptomic levels, dsAllim cotton showed no significant impact on O. similis.DiscussionThese results support the use of dsAllim cotton as a reference in developing regulatory frameworks for the risk assessment of RNAi crops. Together with previous research, our findings underscore the importance of conducting RNAi crop safety evaluations for non-target organisms on a case-by-case basis, with particular attention to potential off-target effects.